Risk factors for progression from severe maternal morbidity to death: a national cohort study - Kayem, G; Kurinczuk, J; Lewis, G; Golightly, S; Brocklehurst, P; Knight, M (Public Library of Science, 2011)
Background Women continue to die unnecessarily during or after pregnancy in the developed world. The aim of this analysis was to compare women with severe maternal morbidities who survived with those who died, to quantify the risk associated with identified factors to inform policy and practice to improve survival.